Wearable Flexible Temperature Sensor Suite for Thermal-Tactile Perception - Krishnan, Athul; Thiyagarajan, Karthick; Kodagoda, Sarath; Bhattacharjee, Mitradip (IEEE sensors journal, 2024)
Qualitative and quantitative analysis of object temperature plays a vital role in wearable technologies and tactile-perception-based applications. It has been the subject of numerous studies for developing soft, bio-compatible, and flexible temperature sensors. When these sensors are encapsulated and integrated with electronic modules for various wearable healthcare monitoring and thermal perception applications, they tend to deviate from their original performances. In this article, we report the design and development of an encapsulated flexible temperature sensor wearable suite based on graphene oxide (GO) + poly(3,4-ethylenedioxythiophene):poly(styr-enesulfonate) (PEDOT:PSS) composite and commercially available nitrile butadiene rubber sheet encapsulation for investigating the encapsulation impacts. The design of the bio-compatible sensor caters to wearable health monitoring systems and thermal perception applications. Due to the implications of sensor encapsulation, experimental results show a 19.15% sensitivity value degradation, a reaction time difference of 0.84 s, and a recovery time difference of 16.5 s when compared with the unencapsulated sensor structure. Furthermore, the encapsulated sensor structure is integrated into a thermal, tactile-perception-based wireless monitoring framework.